Regional, multi-decadal analysis on the Loire River basin reveals that stream temperature increases faster than air temperature - H. Seyedhashemi; H. Seyedhashemi; J.-P. Vidal; J. S. Diamond; D. Thiéry; C. Monteil; F. Hendrickx; A. Maire; F. Moatar (Hydrology and Earth System Sciences, 2022)
Stream temperature appears to be increasing globally, but its rate remains poorly constrained due to a paucity of long-term data and difficulty in parsing effects of hydroclimate and landscape variability. Here, we address these issues using the physically based thermal model T-NET (Temperature-NETwork) coupled with the EROS semi-distributed hydrological model to reconstruct past daily stream temperature and streamflow at the scale of the entire Loire River basin in France (105 km2 with 52 278 reaches).